Efeito das mudanças climáticas, no uso da terra e das invasões biológicas na distribuição de duas espécies de árvores da caatinga - Reis, Daniel Oliveira (2024)
Land-use changes, biological invasions, and climate change are considered the main threats to the conservation of the planet's biodiversity. Thus, this study aimed to understand how the distribution of two native tree species from the Caatinga may be affected by the synergistic effect of these factors. For this, the native species Amburana cearensis (Allemão) A.C.Sm. and Schinopsis brasiliensis Engl. and the exotic invasives Leucaena leucocephala (Lam.) by Wit and Prosopis spp. were chosen. Initially, georeferenced points of these species were obtained from different online databases. After an adjustment process, these points were correlated with climatic variables using GAM, Maxent, RF, and GBM algorithms to create current and future distribution models. The models of native and invasive exotic species were binarized based on the value that maximized the TSS and then summed in pairs for the same period and scenario to calculate the area where native and invasive exotic species may co-occur (overlap) in the Caatinga. Additionally, projections of land use and land cover were obtained to quantify anthropization in the present and future within the overlapping areas between the species. Currently, S. brasiliensis has a suitable area of 702,176 km2, and future projections show reductions in all evaluated periods, especially in 2081-2100, reaching 467,927 km2. A. cearensis, despite experiencing a slight contraction in its suitable area, maintained a constant value of 862,941 km2 according to binary models in all periods and scenarios evaluated. The percentage of anthropization within suitable areas was higher in all future pessimistic scenarios compared to the present. The suitable overlapping area between S. brasiliensis and A. cearenses and the invasive exotic species L. leucocephala decreased from 701,900 and 862,494 km2 in the present to 236,603 and 421,231 km2 in the future, respectively. Similarly, the overlapping area between S. brasiliensis and Prosopis spp. was 702,176 km2 in the present to 467,927 km2 in the future. The overlap between A. cearensis and Prosopis spp. maintained the value of 862,941 km2 throughout the evaluated periods. Despite the contraction of much of the overlapping areas, the trend was an increase in the percentage of anthropization in pessimistic scenarios compared to the current period. Thus, the models obtained suggest that the predicted climate changes in the coming years may decrease the extent of occurrence of native species, especially S. brasiliensis, and the presented scenario could be even worse due to the high spatial overlap between native and invasive exotic species in conservation-favorable conditions for L. leucocephala and Prosopis spp.